SMART MONITORING DAN KONTROL BERBASIS ARDUINO PADA SISTEM AQUAPONIK - Jagad, Lang; Mei Sundari, Ellys; Apriani, Winda (Politeknik Negeri Sriwijaya, 2022)
Improvement in urban agricultural cultivation technology with an aquaponic system has become an alternative for people who have limited land or yard, ranging from efforts to realize family food resilience and economic improvement on a commercial scale. In supporting the success of Aquaponic cultivation, the temperature and water pH conditions greatly affect the growth and development of plants and fish, so the accurate monitoring of temperature and water pH is very important. Therefore, the use of monitoring and control systems in aquaponic cultivation integrated with the Internet of Things (IoT) is expected to be a more efficient solution than conventional cultivation in terms of intelligent and sustainable maintenance and monitoring of the system. All information concerning the state of the system relates to physical parameters such as Temperature and Water PH in the Aquaponic Pool along with the environmental conditions obtained from several installed sensors and sent to the server to provide real-time and real-time information to the user. The result of this research make prototype of realtime condition monitoring device from temperature and pH of water automatically condition of aquaponic based on measurement obtained from installed sensors can be monitored using computer or smartphone.